2002
DOI: 10.1001/archinte.162.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antidepressant Treatment on Chronic Back Pain

Abstract: Antidepressants are more effective than placebo in reducing pain severity but not functional status in chronic back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(91 citation statements)
references
References 48 publications
1
82
0
7
Order By: Relevance
“…Most of these reviews were published [6,42,76,78,83,88,90,135,146,190,192], but preliminary results from one Cochrane review on patient education (A. Engers et al, submitted for publication) that has been submitted for publication were also used. Because no Cochrane review was available, we used two recently published systematic reviews for the evidence summary on antidepressants [161,170]. The Cochrane review on work conditioning, work hardening, and functional restoration [163] was not taken into account because all trials included in this review were also included in the reviews on exercise therapy and multidisciplinary treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these reviews were published [6,42,76,78,83,88,90,135,146,190,192], but preliminary results from one Cochrane review on patient education (A. Engers et al, submitted for publication) that has been submitted for publication were also used. Because no Cochrane review was available, we used two recently published systematic reviews for the evidence summary on antidepressants [161,170]. The Cochrane review on work conditioning, work hardening, and functional restoration [163] was not taken into account because all trials included in this review were also included in the reviews on exercise therapy and multidisciplinary treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The two trials on selective serotonin reuptake inhibitors showed that the latter were not effective. The second review (Salerno et al 2002) concluded that patients with antidepressants were significantly more likely to improve in pain severity than those taking placebo (0.41; 95%confidence interval, 0.22-0.61) but not in activities of daily living (0.24; 95% confidence interval, -0.21-0.69).…”
Section: Effectiveness Versus Placebomentioning
confidence: 99%
“…Two high quality systematic reviews (Salerno et al 2002 concluded that noradrenergic-serotonergic and noradrenergic antidepressants are more effective than selective serotonin reuptake inhibitors (which seem to have no effect).…”
Section: Effectiveness Versus Other Treatm (Only Vs Other Antidepresmentioning
confidence: 99%
“…Two systematic reviews concluded that tricyclic antidepressants have modest beneficial effects on pain but limited effects on functional status (Salerno et al, 2002;Staiger et al, 2003).…”
Section: Adjunctive Therapiesmentioning
confidence: 99%